Patient positioning in anaesthesia. Issue 11 (November 2015) - O'Connor, Dominic; Radcliffe, Jeremy
Abstract: Anaesthesia inhibits a variety of the protective mechanisms which are usually in place to protect us from harm and prevent damage to vulnerable tissues. In addition, anaesthesia may impose physiological stresses on these tissues. Patients are often required to assume positions for surgery which would be intolerable without anaesthesia; these positions may introduce hazards which can lead to injury. Positioning of patients under anaesthesia is an important subject for anaesthetists to consider, since patient positioning has implications upon the patient's physiological responses as well as potentially causing injury to the patient. We describe the considerations for the anaesthetist when positioning the surgical patient. We discuss the positions commonly used for surgical patients and relate the challenges associated with each of these positions; challenges which can be physical as well as physiological. Staffing and equipment provision levels must be commensurate with the degree of physical effort and the complexity predicted in positioning an individual patient. The anaesthetist also needs to consider the relatively restricted access to the patient for intervention when in the prone or lateral positions.